Analysis of tobacco consumption, before and during the COVID-19 pandemic in Peru - Hernández-Vásquez, Akram (2022)
Tobacco consumption is a global health problem that has caused more than 200 million deaths in the last 30 years1. A decrease in global prevalence has been reported in the last two decades due to cost-effective strategies to reduce morbidity and mortality by this cause2. Despite this, 80% of tobacco consumption is observed in low- and middle-income countries3. Several countries report a decrease in tobacco consumption during the COVID-19 pandemic4,5. However, to date, it remains unknown whether these findings are similar in South American countries.